Educar Crianças e Jovens à Luz da Fé e Cultura: as Instituições Escolares Confessionais Católicas na Sociedade Piauiense (1906 a 1973) - Silva, Samara Mendes Araújo (2010)
The Catholic Schools have had decisive participation in the reconfiguration process of the social roles specially the feminine ones because presented and represented to the women (even to the ones who haven´t taken part of their pupils´ groups) the possibility of a profissional and intelectual development which conveyed the enlargement and diversification of the insertion and those women´s social performance, before limited to the home-circle and to the mothercraft and wifelike roles To demonstrate that consequence of the Catholic churches educational action – and aware whereof the social processes and the social individuals actions are in a continuous entrenchment– the Catarinas Sisters Schools in Piauí (from 1906 to 1973) were taken as object of this study and it was analyzed how the educational processes, insertion and social emplacement of the ex-students from those institutions were constituted. By studying the History of Piauiense Feminine Education this research was focused on the History of the Confessional Catholic based on the theoretical-methodological references emanated of the Cultural History and the Historical Sociology – which were important once it was possible to use different historical sources such as (documental hemerographics iconographic and ex-students reports) – it was confirmed that under an apparent silence respect and maintenance of the present social configuration the schoolgirls of the Catholic Confessional Schools contributed without fuss and in a decisive way to the changes of the women´s position and social roles in the piauiense society – and for brazilian and northeastern extension – made known ways of insubordination produced strategies that sometimes discharged in the transformation (slow but progressive) of the social configuration In spite of these women had taken upon lots of alterations of the social roles, they haven´t untied the feminine´s “gifts” and “vocations” of the religiosity motherhood, sweetness, family and marriage still in their daily activities and as a result of the years of intelectual social and religious development acquired in the catholic confessional schools